Global approaches to tackling antimicrobial resistance: a comprehensive analysis of water, sanitation and hygiene policies - Rebecca Katz; Ciara M Weets (BMJ Global Health)
Background Unsafe water, sanitation and hygiene (WASH) contributes to a high burden of disease and exacerbates factors that promote the development of antimicrobial resistance (AMR). Enforceable policies are foundational to curbing inappropriate use of antimicrobials and providing safe WASH. While many countries have established National Action Plans for AMR that include provisions for WASH, few have codified these plans into legally enforceable policy. Here, we provide a comprehensive map and describe the current regulatory environment for WASH.Methods We conducted a comprehensive analysis of the WASH-related policies in 193 countries. Policies were identified, collated, and categorised into a publicly available repository.Results A total of 672 policies met the criteria for inclusion in the dataset. No category of WASH-related policies had been adopted by all countries included in the study. Policy categories that were potentially more difficult to enforce in light of economic and governance limitations tended to be more prevalent and diverse, whereas policies in categories that were highly resource intensive and specific were less universal. Countries with gaps in policy categories also tended to be regionally clustered. While countries in the South Asian and European WHO regions had nearly universal policy coverage across all countries, the presence of policies was inconsistent across countries in the African and Eastern Mediterranean regions.Conclusion While decision-makers should rely on knowing which policies work best to mitigate the burden of WASH-related disease and AMR development, they must first have a comprehensive understanding of the current regulatory environment. Researchers and decision-makers need to know which policies work best and under what circumstances. The global mapping of WASH policies, which may have implications for AMR development, serves as a foundation for future policy analysis for AMR.